Mitochondrial genome of captive Alpine musk deer, Moschus chrysogaster (Moschidae), and phylogenetic analyses with its coordinal species - Chao Yang; Wei-Feng Wang; Xiao-Juan Du; Xiao Tan; Li-Juan Suo; Kun Bian; Fei-Ran Li; Jie Tang; Ben-Mo Jiang; Xue-Juan Li; Yan Wang (Mitochondrial DNA. Part B. Resources, 2021)
Alpine musk deer, Moschus chrysogaster, a solitary, primitive ungulate inhabiting high elevation areas (3000–4500 m) is an endangered species facing threat of extinction globally due to excessive hunting for its musk. In this study, we determined the complete mitochondrial genome of M. chrysogaster, which was 16,354 bp in length, and revealed the same gene order and genomic organization as typical Moschidae mitochondrial DNA. Start codons in 13 protein-coding genes (PCGs) were all typical ATGs except ATA for ND2 and ND3 and ATT for ND5. Stop codons were all typical types except an incomplete stop codon T for COX3, ND2, ND3, and ND4. Secondary structures in 22 transfer RNA genes all showed typical cloverleaf except tRNA-Ser (AGY), in which the dihydrouridine arm formed a simple loop. No repeat units were found in the control region. The topology structure indicated that M. cupreus was primitive and located at the root of the Moschidae clade. Phylogenetic reconstruction placed M. chrysogaster as a distinct lineage, closely related to the branch of M. leucogaster, M. berezovskii (wild) and predicted a sister relationship with M. moschiferus, M. anhuiensis, and M. berezovskii (captive). However, we suggested that the genetic resources of M. chrysogaster_JQ608470 should be further investigated.